Prospek Budidaya Maggot (Larva Black Soldier Fly) untuk Membangun Ekonomi Desa dan Mengurangi Sampah Rumah Tangga - Hakim, Mukti; Balatif, Fuad; Siregar, Ira Pratiwii (JURNAL AGROPLASMA, 2023)
Indonesia has quite serious environmental problems, one of which is the waste problem, waste production in Indonesia is always increasing every day, both organic and inorganic waste. One of the organic waste recycling techniques is the bioconversion method. Organisms that play a role in the bioconversion process can be fungi or insect larvae. These BSF larvae are known as maggots or "maggots". Aras Kabu Village is one of the villages in the Beringin sub-district, Deli Serdang Regency. Population growth was 1.86% from 2015. The purpose of this research was to analyze the Prospects for Cultivating Maggot (Black Soldier Fly Larvae) to Build the Village Economy and Reduce Household Waste in Aras Kabu Village, Beringin District, Deli Serdang Regency. This research was conducted in Aras kabu village from October to November 2022. This research was conducted using an experimental method. The experimental method used was to determine the amount of maggot that could be produced from household waste. The results of the experimental method for making maggot will be used to calculate the amount of maggot that can be produced in Aras Kabu Village if all the remaining household waste can be collected. The number of families in Aras Kabu Village is 186 families. The results showed that the calculation of the Revenue Cost Ratio per month in the mangosteen cultivation business in Aras Kabu Village, Beringin District, Deli Serdang Regency obtained a result of 10.42. This means that there are prospects for the mangosteen cultivation business in Aras Kabu Village, Beringin District, Deli Serdang Regency, which is feasible to runKeywords: Village Economy, BSF Maggot, Household Waste